Assessing the Decade After: A Critical Analysis of Responsibility to Protect (R2P) in the Libya Intervention - Estriani, Heavy Nala (Hasanuddin University, 2023)
Currently, 12 years post-NATO intervention, Libya falls into the category of a fragile state, with worsening indices in the economic, security, and social aspects since 2011. While not a new topic, the situation in Libya in 2011 can always serve as a lesson and exemplification of the discourse on humanitarian intervention, specifically the principal aspects of Responsibility to Protect (R2P). The current situation in Libya raises questions about whether there were flaws in the military intervention carried out by the NATO alliance in 2011. This paper aims to analyze the just ad bellum features related to the principal aspects within R2P were implemented in the NATO intervention in Libya. Thus, this study argues that the failure of the military intervention in Libya is due to the non-fulfillment of the basic aspects of Responsibility to Protect (R2P), especially in relation to just ad bellum, such as right authority, last resort, just cause, right intention, proportional means, and reasonable prospects in carrying out humanitarian intervention.